Polyvictimization and Post-Traumatic Symptomatology: The Role of Social Support and Self-Efficacy - Guerra, Cristóbal; Inostroza, Romina; Villegas, Jaime; Villalobos, Leticia; Pinto-Cortez, Cristián (Revista de Psicología, 2017)
Internationally, there is evidence that poly-victimization in childhood –exposure to different types of violence– has negative consequences for individuals even into adulthood. The consequences would be more severe than repeated exposure to a specific type of violence. In Chile there is not enough research on this phenomenon. For this reason, the objective of the study is to evaluate the relationship between poly-victimization, posttraumatic symptomatology, self-efficacy and social support in a sample of 180 university students (M = 20.72, SD = 3.10). We performed both bivariate (correlations) and multivariate analyzes (multiple regression and path analysis). The results show a direct relationship between poly-victimization and posttraumatic symptomatology. In addition, self-efficacy mediated the relationship between social support and symptomatology: the greater the social support, the greater the self-efficacy, and thus the less symptomatology. We discuss the implications of these results for the psychotherapy processes with adult population with mental health problems.